Computationally Efficient Scale Covariant Time-Frequency Distributions. (18th February 2009) - Aviyente, Selin
Abstract : Scale is a physical attribute of a signal which occurs in many natural settings. Time-frequency distributions (TFDs) belonging to Cohen's class are invariant to time and frequency shifts, but are not necessarily covariant to the time scalings of the signal. Conditions on the time-frequency kernel for yielding a scale covariant distribution have been previously derived (Cohen, 1995). In this paper, a new class of computationally efficient scale covariant distributions is introduced. These distributions are constructed using the eigendecomposition of time-frequency kernels (Burrus et al., 1997). The performance of this new class of distributions is illustrated with examples and is compared to conventional scale covariant distributions.